AB0098 Association between genetics variants in il15 and disease activity, radiological progression and treatment requirements in patients with early arthritis - Garcia-Arias, M.; Lamana, A.; Ortiz, A. M.; González-Álvaro, I.; García-Vicuña, R. (Annals of the rheumatic diseases, 2013)
Background Recently, Knevel et al have described the association between five single nucleotide polymorphisms (SNPs) in the IL-15 gene with differences in the radiological progression in patients with rheumatoid arthritis (RA) (1). In this context, our group have described the association between elevated serum levels of IL-15 with a worse clinical outcome and a higher requirement of treatment in patients with early arthritis (EA) (2). Objectives To analysed if the SNPs in the IL-15 gene associated with a higher radiological progression are associated with disease activity and the intensity of treatment in a cohort of EA. Methods Data of 171 patients with EA previously described (2) were analysed. Genomic DNA from blood samples was isolated using the system MagNA Pure LC DNA Isolation (Roche Molecular Biochemicals, Penzberg, Germany). The genotyping of rs2322182, rs4371699, rs6821171, rs7665842 and rs 7667746 was performed using specific Taq-Man probes (Applied Biosystems, Foster City, CA, USA), using the polymerase chain reaction in a thermocycler 7900 HT Real-Time. Disease activity was determined by the HUPI index (3), radiological evaluation was assessed by the method of Van der Heijde modified by Sharp and treatment intensity was quantified as the number of days of treatment with disease-modifying antirheumatic drug in the first two years of follow-up (2). To determine the influence of the SNPs in the disease activity, a multivariable longitudinal analysis adjusted for patient and visit was performed using the STATA 12 xtgee command. Generalized linear models (glm of STATA 12 command) were used to study the association with radiological progression and the intensity of treatment. Results Homozygous patients for minor alleles in the SNP rs7665842 (genotype CC; p < 0.01) and rs7667746 (genotype CC; p = 0.02) presented a higher radiological progression. A similar but a non-significant trend was found with the rs4371699. Disease activity was higher in homozygous patients for the minor allele of rs2322182 (genotype GG) as well as those carriers of, at least, a T allele of rs7667746 (p = 0.044 and p = 0.06, respectively). Also, patients with a T allele of rs7665842 presented a non-significant trend in this line. However, the treatment was significantly more intense in homozygous patients for the minor allele of rs7665842 (genotype TT; p = 0.05) and a similar trend was observed for the rs7667746, without reaching statistical significance. None of the other SNPs studied by Knevel et al (2) was significantly associated with the variables of our analysis. Conclusions Our results reproduce, in part, those described by Knevel et al (2), since they demonstrate a higher radiological progression in homozygous patients for C allele in the SNP rs7665842 and rs7667746. However, the patients with the opposite allele (T) of those SNPs presented higher disease activity and receive more treatment. As a result, these patients may present a lower radiological progression. References Knevel et al. Ann Rheum Dis 2012; 71: 1651-7; Gonzalez-Alvaro et al. PLoS ONE 2011; 6: e29492; Castrejon et al. Arthritis Care Res 2013 (in press, PMID 23002022) Acknowledgements Program RD08/0075 (RIER), FIS PI11/00551 of the Health Institute Carlos III (ISCIII) and research support from UCB Pharmaceuticals (Unrestricted grant). Disclosure of Interest None Declared